Prediction of interfacial fracture between concrete and fiber reinforced polymer (FRP) by using cohesive zone modeling. (October 2015) - Park, Kyoungsoo; Ha, Kyungsu; Choi, Habeun; Lee, Changjoon
Abstract: Interfacial debonding between concrete and fiber reinforced polymer (FRP) is investigated through integrating experiments and computations. An experimental program is designed to evaluate interfacial fracture parameters of mode-I through cutting and bonding specimens with an FRP sheet. The evaluated fracture parameters, i.e. the fracture energy and the bonding strength, are confirmed by predicting FRP debonding failure with the cohesive zone modeling approach. In the cohesive zone model, a traction-separation relation for FRP debonding is proposed with a shape index while providing various initial descending slopes. Computational results of the cohesive zone model agree well with three-point bending test results for both FRP debonding and plain concrete fracture. Furthermore, both experimental and computational results demonstrate that the fracture energy and the cohesive strength are essential fracture parameters for the prediction of FRP debonding behavior.